2021
DOI: 10.1210/clinem/dgab762
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence Trends of Diabetes Subgroups in the United States: A Data-driven Analysis Spanning Three Decades From NHANES (1988-2018)

Abstract: Aims Data-driven diabetes subgroups were proposed as an alternative to address diabetes heterogeneity. However, changes in trends for these subgroups have not been reported. Here, we analyzed trends of diabetes subgroups, stratified by sex, race, education level, age categories and time since diabetes diagnosis in the U.S. Methods We used data from consecutive NHANES cycles spanning the 1988-2018 period. Diabetes subgroups (m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…This population-based report suggests broad genetic influences. The findings in the current analysis were consistent and robust for the observed differences in age, sex, and ethnicity ( 24 , 28 31 ).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This population-based report suggests broad genetic influences. The findings in the current analysis were consistent and robust for the observed differences in age, sex, and ethnicity ( 24 , 28 31 ).…”
Section: Discussionsupporting
confidence: 80%
“…For demographic characteristics, reports have confirmed that the biological factors affecting the pathophysiology of diabetes differ from race or nationality, and may be influenced by social factors, such as different cultural backgrounds ( 17 24 ). Data from the Centers for Disease Control and Prevention shows that the probability of some racial and ethnic groups being diagnosed with diabetes in the USA is much higher than that of whites, which was reviewed in Lancet ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the abbreviated model, 4 of the 5 most influential features on an increased PTA were known risk factors for the development of HL: older age, male gender, cigarette smoking, and obesity 32‐36 . With the rising prevalence of obesity and diabetes mellitus, the impact of these conditions on HL remains an important consideration 37‐39 . These are health behavior and medical conditions that are routinely documented during clinic visits in primary and specialty care settings and available within the EMR.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of T2D is 66% higher in US Hispanic/Latino persons than in their Non-Hispanic White (NHW) counterparts [ 1 ]. The age and sex-standardized prevalence for impaired fasting glucose (excluding those with a diagnosis of T2D) is 31.6% in Mexican-Americans compared to 26.1% in NHW.…”
Section: Introductionmentioning
confidence: 99%